Competitive sorption of heavy metals by water hyacinth roots. (December 2016) - Zheng, Jia-Chuan; Liu, Hou-Qi; Feng, Hui-Min; Li, Wen-Wei; Lam, Michael Hon-Wah; Lam, Paul Kwan-Sing; Yu, Han-Qing
Abstract: Heavy metal pollution is a global issue severely constraining aquaculture practices, not only deteriorating the aquatic environment but also threatening the aquaculture production. One promising solution is adopting aquaponics systems where a synergy can be established between aquaculture and aquatic plants for metal sorption, but the interactions of multiple metals in such aquatic plants are poorly understood. In this study, we investigated the absorption behaviors of Cu(II) and Cd(II) in water by water hyacinth roots in both single- and binary-metal systems. Cu(II) and Cd(II) were individually removed by water hyacinth roots at high efficiency, accompanied with release of protons and cations such as Ca 2+ and Mg 2+ . However, in a binary-metal arrangement, the Cd(II) sorption was significantly inhibited by Cu(II), and the higher sorption affinity of Cu(II) accounted for its competitive sorption advantage. Ionic exchange was identified as a predominant mechanism of the metal sorption by water hyacinth roots, and the amine and oxygen-containing groups are the main binding sites accounting for metal sorption via chelation or coordination. This study highlights the interactive impacts of different metals during their sorption by water hyacinth roots and elucidates the underlying mechanism of metal competitive sorption, which may provide useful implications for optimization of phytoremediation system and development of more sustainable aquaculture industry. Graphical abstract: Highlights: Cu(II) was preferentially absorbed by water hyacinth roots over Cd(II). Metal absorption mainly occurred via ionic exchange mechanism. Amine and oxygen-containing groups contributed to metal uptake via chelation. Competitive metal sorption could affect phytoremediation in aquaponics system. Abstract : Preferential absorption of Cu(II) over Cd(II) by water hyacinth roots was attributed to a stronger binding affinity to Cu(II) and was realized through an ionic exchange mechanism.